The Effect of Optimism, Happiness and Self-esteem on Quality of Life among Yemeni University Students - Ahmed Gamal Ahmed Gawas (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2024)
There has been a lack of research in the area of positive psychology variables in the Yemeni context. For this reason, the current research aims to examine the effect of optimism, happiness, self-esteem, on quality of life among Yemeni university students. It also seeks to test whether self-esteem mediates the relationship between optimism and quality of life. 657 Yemeni university students participated in this study. Positive personality index with three-dimensional (optimism, happiness and quality of life) and Rosenberg self-esteem scale were used. The results revealed a positive correlation between optimism, happiness, self-esteem and quality of life. Quality of life was predicted from happiness, optimism, and self-esteem. The results revealed that self-esteem partially mediates the relationship between optimism and quality of life. Also, results showed differences in happiness, self-esteem, and quality of life due to gender. However, the results did not reveal any differences on study variables due to social status or income level.